State regulation versus co-management: evidence from the Cochin Estuarine Fisheries in India - JEENA T. SRINIVASAN (Environment and Development Economics 10: 97-117 C 2005, 2005)
This paper examines the property rights of the Cochin estuarine fisheries in India, which in spite of having well-defined access and conservation rules imposed by the state, have failed to ensure proper resource management. Considering the resource characteristics and the causes for state's failure, co-management, which requires a redefinition of management functions by state as well as users, has been proposed as an alternative. Analysis of user characteristics, using the two-stage estimation procedure, throws policy signals that under co-management the state can strengthen the licensing system to restrict access to fishing and to impart awareness regarding conservation rules. The logit analysis on users' role indicates that, although certain types of heterogeneities contribute towards the critical mass needed for a collective action, the distributional implications may lead at least some to oppose co-management. This implies that, even if users initially get to agree to co-operate and share any rents fromconservation, significant prisoner's dilemma will soon occur returning the resource to its current state, and comanagement will have to still grapple with lack of well-defined property rights.